[PP.37.15] CLINICAL PRESENTATION OF PATIENTS WITH FIBROMUSCULAR DYSPLASIA ACCORDING TO THE NUMBER OF VASCUALR BEDS AFFECTED: THE PRELIMINARY DATA OF THE POLISH REGISTRY FOR FIBROMUSCULAR DYSPLASIA. (September 2016) - Jozwik-Plebanek, K.; Januszewicz, M.; Wojcik, W.; Warchol-Celinska, E.; Hanus, K.; Michalowska, I.; Florczak, E.; Prejbisz, A.; Kabat, M.; Janaszek-Sitkowska, H.; Andziak, P.; Stryczynski, L.; et al.
Abstract : Objective: To present and compare clinical characteristics of patients with fibromuscular dysplasia (FMD) in one and two or more vascular beds Design and method: 84 patients (59F, 25 M, mean age:42.5 ± 14.8 years, range:18–72) with confirmed FMD in any vascular bed were enrolled in 2015 in ARCADIA-POL registry (instituted as Polish-French collaboration). All patients underwent evaluation including ambulatory blood pressure monitoring, biochemical evaluation, biobanking, duplex Doppler of carotid and abdominal arteries and whole body angio-CT. In this analysis we divided patients into two groups according to the number of vascular beds affected – Group 1 (patients with FMD in one vascular bed) and Group 2 (patients with FMD in two or more vascular beds) Results: Of 84 patients with established FMD, 45 pts(53.6%) had one vascular bed affected (Group 1) and 39pts(46.4%) had two or more vascular bed affected (Group 2). Patients in group 2 as compared with group 1 were significantly older (46.1 ± 14.5vs.39.4 ± 14.4, p = 0.037) and were characterized by non-significantly higher rate of females (79.5vs.62.2%; p = 0.084). At evaluation there were no difference in frequency of smokers, hypertension rate, median number of antihypertensive medications, nor in office and 24-hour blood pressure values. Patients in group 2 differed significantly in median age at diagnosis of FMD (41.9 ± 14.8 vs.34.4 ± 15.9 ys, p = 0.038) and hypertension (35.9 ± 14.8 vs.27.9 ± 13.9 ys, p = 0.024) as compared to group 1. Bilateral renal artery FMD lesions were non-significantly higher in patients in group 2 (43.6% vs. 26.7%, p = 0.104). Patients in group 2 were characterized by significantly higher frequency of aneurysms in any artery (43.6vs.11.4%, p = 0.001) and non- significantly higher incidence of artery dissection (21.1%vs.9.1%, p = 0.126) as compared to group 1. There was no difference in the incidence of dissection of any artery between the groups. In multiple logistic regression analysis the only predictor of an involvement of two and more vascular beds was the presence of aneurysm Conclusions: Patients with FMD confirmed in two or more vascular bed were older and were characterized by older age at diagnosis of FMD and hypertension as well as higher incidence of aneurysm as compared to patients with FMD affecting only one vascular bed